Penerapan Pendekatan Tesu untuk Meningkatkan Hasil Belajar Muatan Pelajaran PPKn Materi Mengenal Perbedaan Suku pada Siswa Kelas 2 SDN Alang-alang Caruban 1 - Zuliatin, Luluk (Universitas Nusantara PGRI Kediri, 2021)
The low learning outcomes of Civics subjects in grade 2 students of SDN Alang-alang Caruban 1 became the background for conducting classroom action research. The strategies that have been carried out have not been able to improve students' reading skills. Through the new learning innovation, research was conducted using the Tesu Approach to help improve Civics learning outcomes. The research was conducted on 2nd grade students of SDN Alang-alang Caruban 1 with 19 students receiving the same treatment. The research was carried out in 2 cycles, each cycle being carried out in 1 meeting. The results obtained in cycle 1 are 74% of students are able to work on questions and get scores above the KKM, the rest have not reached the KKM. However, in cycle 2 there was an increase until there were 89% of students completed in learning. Weaknesses of students in the ability to memorize ethnic differences. Based on the research results, it is proven that the Tesu approach can help teachers in an effort to improve Civics learning outcomes for grade 2 students.